Correlations Between the Crown Sizes, Pruning Times and Fruit Quality of Sour Cherry Cultivars - Király, Katalin (Acta Agraria Debreceniensis, 2005)
To increase the intensiveness of sour cherry production, i.e. the use of smaller trees, it is necessary to adopt growth-moderating techniques rather than using dwarfing rootstocks. Apart from the traditional technique of using rootstocks that support stronger growth, new or rarely-used techniques and methods must be adopted. Pruning should be carried out in the summer rather than in the winter, the optimal period being 1-3 weeks after harvest. A combination of the increase in favourable exposure-time and smaller crown sizes make higher tree densities (tree/ha) and better utilisation of the crown (specific cropload) possible. The systematic use of summer pruning leads to better quality fruit.